Food Safety Knowledge and Behaviors of Women, Infant, and Children (WIC) Program Participants in the United States - Kwon, Junehee; Wilson, Amber N.S.; Bednar, Carolyn; Kennon, Lisa (My University, 2010)
Although the incidence of foodborne illnesses has declined, thousands of cases are still reported in the United States. In conjunction with industry efforts to reduce foodborne pathogens, consumers play an important role in decreasing foodborne illnesses. To assess food safety knowledge and food handling behaviors of low-income, high-risk populations, a study was conducted with participants of the Special Supplemental Food Program for Women, Infants, and Children (WIC). A survey was conducted with 1,598 clients from 87 WIC agencies nationwide. Descriptive statistics, chi-square analyses, t tests, and analyses of variance were calculated. A majority of respondents received food safety information from WIC (78.7%), family (63.1%), and television (60.7%). Most respondents recognized the necessity for washing and sanitizing cutting boards and utensils (94.3%), but only 66.1% knew the correct ways to sanitize. Using a thermometer to ensure doneness of meat was least recognized (23.7%) and used by even fewer respondents (7.7%). The majority (77.4%) used color of meat and/or juices when checking the doneness of ground beef items. Over half of the respondents (58.4%) used acceptable thawing methods, but many thawed frozen meats on the counter (21.0%) or in a sink filled with water (20.6%). There were significant differences in thawing methods, overall knowledge scores, and overall behavior scores among different racial and ethnic groups. White respondents had higher knowledge scores than did Hispanics, and blacks had lower behavior scores than did individuals in the other racial and ethnic groups. Results of the study suggested the need for food safety education for low-income consumers and different messages to be delivered to specific demographic groups.
Keywords: Handling behaviors; Consumers; Perceptions; Attitudes; Food safety; Foodborne illness